Consumer interpretation of ready to drink orange juice and nectar labelling - Alessandra, Ferrarezi [UNESP]; Karina Olbrich, Dos Santos; Magali, Monteiro [UNESP] (Oxford University Press (OUP), 2013)
The aim of this study was to evaluate consumers' use and interpretation of ready to drink orange juice and nectar label information and its influence on the purchase decision. One hundred and sixty-seven consumers of ready to drink orange juice and nectar were interviewed. The labels were analysed to evaluate their conformance to Brazilian legislation. The manufacturing and shelf life date were the information most often checked, followed by health related issues. Brand, price and flavour were the most important factors for purchase decision. Brand and flavour showed significant association with consumer age. For most interviewed, 'nectar', 'whole' and 'natural' or '100% natural' were not well understood; they were not in accordance with the Brazilian legislation. 'Nectar', 'whole' and 'natural' or '100% natural' received a positive interpretation, whereas 'reconstituted juice' was considered a negative expression. Nevertheless, none of the labels completely conformed to the specific nutritional labelling legislation. © 2013 Institute of Food Science and Technology.
Keywords: Citrus sinensis; Food labelling; Food labelling legislation; Fruit beverages; Label information; Nutritional labelling; Orange juice; Purchase decision; Shelf life; Food technology; Fruit juices